2018
DOI: 10.1016/j.ijid.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of tuberculosis among patients following treatment completion in eight provinces of Vietnam: A nested case-control study

Abstract: Index disease treatment history is a leading determinant of relapse among patients with TB in Vietnam. Further research is required to identify interventions that will reduce the risk of recurrent disease and enhance its early detection within high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
1
20
1
Order By: Relevance
“…In this study, though treatment outcome as per WHO definition is found to be good, the use of retrospective secondary data may affect the success rate because it was totally dependent on the documented data in the TB DOTS registration logbook and cannot control the outcome. As we didn't have available smear test results, the vast majority of successful cases (70.2%) were categorized as "treatment completed" and which is actually reported as risk for treatment relapse [31,32]. Being a single-center study, the results may not be generalized to all other health centers situated in Addis Ababa.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, though treatment outcome as per WHO definition is found to be good, the use of retrospective secondary data may affect the success rate because it was totally dependent on the documented data in the TB DOTS registration logbook and cannot control the outcome. As we didn't have available smear test results, the vast majority of successful cases (70.2%) were categorized as "treatment completed" and which is actually reported as risk for treatment relapse [31,32]. Being a single-center study, the results may not be generalized to all other health centers situated in Addis Ababa.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to age, the other predictive factor for recurrence among TB patients treated in Serveis Clínics was resistance to at least one anti-TB drug. In China and Vietnam, an association was found between MDR and TB recurrence [37,38], while TB recurrences among South African miners were associated with anti-TB drug resistance [39]. In Uzbekistan, resistance to treatment was also found to substantially contribute to TB recurrences [40].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have analyzed the effect of a prior TB episode. A case-control study conducted in Vietnam concluded that one of the factors associated with recurrence was having reported a prior history of TB [38]. A previous study conducted in Barcelona reported that a history of TB treatment before study inclusion was a risk factor for recurrence [14].…”
Section: Discussionmentioning
confidence: 99%
“…In observational datasets from Russia and the USA, this association extends to the development of drug resistance [51,52], although in simulations it has not been consistently proven [53]. Recurrence of TB disease among pulmonary TB patients was higher with worse implementation in both the Yemen and Vietnam [54,55].…”
Section: Suboptimal Implementationmentioning
confidence: 99%